Methods for dose quantification in continuous renal replacement therapy: Toward a more precise approach. Issue 11 (18th August 2021) - Villa, Gianluca; Fabbri, Sergio; Samoni, Sara; Cecchi, Matteo; Fioccola, Antonio; Scirè‐Calabrisotto, Caterina; Mari, Gaia; Pomarè Montin, Diego; Romagnoli, Stefano
Abstract: Periodic dose assessment is quintessential for dynamic dose adjustment and quality control of continuous renal replacement therapy (CRRT) in critically ill patients with acute kidney injury (AKI). The flows‐based methods to estimate dose are easy and reproducible methods to quantify (estimate) CRRT dose at the bedside. In particular, quantification of effluent flow and, mainly, the current dose (adjusted for dialysate, replacement, blood flows, and net ultrafiltration) is routinely used in clinical practice. Unfortunately, these methods are critically influenced by several external unpredictable factors; the estimated dose often overestimates the real biological delivered dose quantified through the measurement of urea clearance (the current effective delivered dose ). Although the current effective delivered dose is undoubtedly more precise than the flows‐based dose estimation in quantifying CRRT efficacy, some limitations are reported for the urea‐based measurement of dose. This article aims to describe the standard of practice for dose quantification in critically ill patients with AKI undergoing CRRT in the intensive care unit. Pitfalls of current methods will be underlined, along with solutions potentially applicable to obtain more precise results in terms of (a) adequate marker solutes that should be used in accordance with the clinical scenario, (b) correct sampling procedures depending on the chosen indicator of transmembrane removal, (c) formulas for calculations, and (d) quality controls and benchmark indicators. Abstract : The periodic dose assessment is quintessential for dynamic dose adjustment and quality control of continuous renal replacement therapy (CRRT) in critically ill patients with acute kidney injury (AKI). The effluent flow quantification and the current dose, easy and reproducible flows‐based dose estimations to quantify the CRRT dose at the bedside, are influenced by external unpredictable factors. Thus, the current effective delivered dose, commonly quantified through the urea clearance measurement, is often overestimated. Limitations related to the urea as it is used as the marker solute could be overcome using different marker solutes (X solutes).